2013
DOI: 10.1186/1479-5876-11-189
|View full text |Cite
|
Sign up to set email alerts
|

Impact of baseline and nadir neutrophil index in non-small cell lung cancer and ovarian cancer patients: Assessment of chemotherapy for resolution of unfavourable neutrophilia

Abstract: BackgroundChronic inflammation has been recognized to foster tumour development. Whether chemotherapy can be used to neutralize chronic inflammation is unclear.MethodsWe evaluated baseline and nadir neutrophils in 111 patients (pts.) with non-small cell lung cancer (NSCLC) and 118 pts. with ovarian cancer (OC) treated with chemotherapy administered with dose-individualization to achieve nadir neutropenia of 1.5. We used predefined baseline neutrophil cut-offs 4.5 × 109/L (NSCLC) and 3.9 × 109/L (OC).ResultsAbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
5
18
1
Order By: Relevance
“…Similarly, it has been suggested that neutropenia is associated with good prognosis in first-line treatment for other types of cancers [15][16][17][18][19][20][21][22][23][24][25]. In addition, in the present study, all patients in the first-line treatment group exhibited prolonged OS for grades 1-3, with particularly good survival for grades 2 and 3.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Similarly, it has been suggested that neutropenia is associated with good prognosis in first-line treatment for other types of cancers [15][16][17][18][19][20][21][22][23][24][25]. In addition, in the present study, all patients in the first-line treatment group exhibited prolonged OS for grades 1-3, with particularly good survival for grades 2 and 3.…”
Section: Discussionsupporting
confidence: 44%
“…Subsequent reports described similar outcomes for nonsmall cell lung cancer [17][18][19], gastric cancer [20], colorectal cancer [21,22], and ovarian cancer [19,23]. These reports suggest that neutropenia could be a predictive factor of treatment responsiveness.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Because an association between C-iN and improved PFS was not observed, post-progression therapy may have a greater, if as yet poorly understood, impact among neutropenic patients, but this is just conjecture. Nevertheless, these results are consistent with the observations reported by others who have noted that C-iN is positively correlated with patient outcomes in a variety of solid tumors including non-small cell lung, colorectal, gastric, breast, cervical, and ovarian cancer [11][12][13][14][15][16][17][18][19][20][21]. Shitara et al conducted a meta-analysis comprised of 9528 patients from 13 prospective and retrospective studies that evaluated neutropenia or leucopenia as a prognostic factor for survival [21].…”
Section: Discussionsupporting
confidence: 86%
“…Cancer may induce an inflammatory state, resulting in multiple inflammatory cells being recruited to the cancer microenvironment, and contributing to the hallmarks of cancer (16,17). Notably, indexes of inflammatory cells [including the pretreatment neutrophil count (PNC), macrophage, neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR)] in the bloodstream can reflect the scope and extent of inflammation (18,19). Previous studies have reported that elevations in the PNC, NLR or PLR indicate a poor prognosis in various human cancer types, most notably in colorectal cancer (19), hepatocellular carcinoma (20), and in gastric (21), esophageal (22), breast (23,24), ovarian (25), cervical (26) and lung cancer (27,28).…”
Section: Introductionmentioning
confidence: 99%